High-Speed Broadband and Academic Achievement in Teenagers: Evidence from Sweden - Erik Grenestam; Martin Nordin (Lund University, School of Economics and Management, Department of Economics, 2018)
This study examines the effects of super-fast internet connections on the academic achievement of students in upper secondary school. We link detailed register data on around 250,000 students to local levels of access to optic fiber broadband and estimate the effect of broadband on student GPA. We show that reaching full coverage in the student's parish of residence causes a GPA reduction ranging from 3 to 6 percent of a standard deviation. Estimates are consistently more negative for boys and students with low ability and/or low-educated parents. Using PISA survey data, we provide evidence that students living in areas with faster broadband expansion also saw a greater increase in the number of hours spent online during weekdays, suggesting student time use as a mechanism.
Keywords: H52; I24; I28; J24; O33; 330; Education; Broadband; Internet; High-school; GPA